2010
DOI: 10.2147/ijn.s12415
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of 5-fluorouracil nanoparticles by supercritical antisolvents for pulmonary delivery

Abstract: This study concerns the supercritical antisolvent process which allows single-step production of 5-fluorouracil (5-FU) nanoparticles. This process enhances the physical characteristics of 5-FU in order to deliver it directly to the respiratory tract. Several mixtures of methanol with dichloromethane, acetone, or ethanol were used for particle preparation, and their effects on the physical characteristics of the final products were studied. The conditions of the experiment included pressures of 100 and 150 bar,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 32 publications
3
23
0
Order By: Relevance
“…20,25 Moreover, the peak at 601 cm -1 was attributed to the P-O-P stretching mode of PO 3À 4 . These absorption bands revealed the presence of the PO 4 3-group in the HAP structure. For 5FU, the absorption bands at 1726, 1670, and 1247 cm -1 are responsible for cyclic imide (CO-NH-CO), imide, amide I band (C ¼ O), and amide III band (C ¼ O), respectively.…”
Section: Characterization Of Hap-5fu Particlesmentioning
confidence: 90%
“…20,25 Moreover, the peak at 601 cm -1 was attributed to the P-O-P stretching mode of PO 3À 4 . These absorption bands revealed the presence of the PO 4 3-group in the HAP structure. For 5FU, the absorption bands at 1726, 1670, and 1247 cm -1 are responsible for cyclic imide (CO-NH-CO), imide, amide I band (C ¼ O), and amide III band (C ¼ O), respectively.…”
Section: Characterization Of Hap-5fu Particlesmentioning
confidence: 90%
“…Also, a type of polylactic acid nanoparticles loaded with docetaxel showed anti-metastatic effect on lung cancer cells (Anton et al 2008). 5-Fluorouracil (5-FU) is another chemotherapeutic drug which has been restricted by its systemic toxicities, severe gastrointestinal toxicities, hematologic side effects and severe bone marrow disturbances (Kalantarian et al 2010). Many studies demonstrated that 5-FU-loaded nanoparticles have a great potential for drug delivery and a good antitumor activity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, tumor cells often undergo significant development of drug resistance. These problems lead to the need of high doses of 5-FU, so its use has been restricted by its systemic toxicities, as severe gastrointestinal toxicities, hematologic side effects and severe bone marrow disturbances [8].…”
Section: Introductionmentioning
confidence: 99%